2018
DOI: 10.1016/j.celrep.2018.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus Mounts a Two-Pronged Attack on Host RNA Polymerase II Transcription

Abstract: SummaryInfluenza virus intimately associates with host RNA polymerase II (Pol II) and mRNA processing machinery. Here, we use mammalian native elongating transcript sequencing (mNET-seq) to examine Pol II behavior during viral infection. We show that influenza virus executes a two-pronged attack on host transcription. First, viral infection causes decreased Pol II gene occupancy downstream of transcription start sites. Second, virus-induced cellular stress leads to a catastrophic failure of Pol II termination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
113
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(139 citation statements)
references
References 74 publications
16
113
1
Order By: Relevance
“…While a combination of viral factors could be responsible for this global shutoff of host transcription, our data suggest that NS1 might be associated with this phenomenon. There is evidence in the literature that IAV infection results in reduced host transcription and mRNA processing by inhibiting the host RNA polymerase II (Pol II) function (60,61). Related to this, a recent study found that several strains of IAV elicit global deregulation of Poll II transcription termination by impairing 3=-end cleavage and termination, and this effect was dependent on NS1 expression (62).…”
Section: Discussionmentioning
confidence: 99%
“…While a combination of viral factors could be responsible for this global shutoff of host transcription, our data suggest that NS1 might be associated with this phenomenon. There is evidence in the literature that IAV infection results in reduced host transcription and mRNA processing by inhibiting the host RNA polymerase II (Pol II) function (60,61). Related to this, a recent study found that several strains of IAV elicit global deregulation of Poll II transcription termination by impairing 3=-end cleavage and termination, and this effect was dependent on NS1 expression (62).…”
Section: Discussionmentioning
confidence: 99%
“…Defective termination of Pol II transcription in response to cell stress has been reported (11)(12)(13)(14)(15). During normal termination of mRNA transcription in mammalian cells, the polymerase accumulates just downstream of the 3= end of most genes, which can be detected in Pol II ChIP-seq and native elongating transcript sequencing (NET-seq) assays (16)(17)(18).…”
mentioning
confidence: 99%
“…DoG genes showed significant enrichments for specific gene ontologies (GOs), including translation initiation and ribosome biogenesis, viral process, response to stress, mitochondrial gene expression, and chromatin organization ( Figure 3D, Figure S3B). The appearance of stress-related and viral-related GOs is notable given precedents for DoG transcription triggered upon environmental stresses and viral infections (Bauer et al, 2018;Cardiello et al, 2018;Hennig et al, 2018;Vilborg et al, 2015;Vilborg et al, 2017).…”
Section: Dog Transcription Affects a Specific Subset Of Stress-responmentioning
confidence: 99%
“…DoG genes were enriched for GOs related to protein translation and response to cellular stress, consistent with our observation of a broad cellular response characterized by increased ribosome biogenesis, protein translation, mitochondrial respiration, and ATP synthesis ( Figure 6). Interestingly, DoG transcription has been observed in response to a range of cellular stresses including oxidative stress (Giannakakis et al, 2015;Vilborg et al, 2017), heat shock (Cardiello et al, 2018;Vilborg et al, 2017), and osmotic stress (Vilborg et al, 2015;Vilborg et al, 2017), in addition to viral infections (Bauer et al, 2018;Heinz et al, 2018;Hennig et al, 2018). However, the mechanisms underlying DoG transcription are not clear.…”
Section: Pladb-induced Transcriptional Alterations Resemble Other Strmentioning
confidence: 99%